DFT study of condensation mechanisms of 4-pyridinecarboxaldehyde with o-, m-, p-aminobenzoic acids - Ion Arsene; Eduard Coropceanu; Viorica Purcel (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
It was theoretically studied the mechanism of the condensation reaction of 4-pyridinecarbo\-xaldehyde with o-, m- and p-aminobenzoic acids. Theoretical calculations represent a primary advantage in studying these reactions, along with the determination of a wide range of molecular properties. The studied reactions take place in two stages, each stage is accompanied by a transition state and for each stage it is calculated the activation energy. Thermodynamically speaking, all reactions are endothermic and the most convenient from an energetic point of view is the reaction for obtaining 4-(pyridine-3-yl-methylene amino) benzoic acid in methanol with an energy value of 9.98 kcal/mol.